2013
DOI: 10.1089/ten.tea.2012.0190
|View full text |Cite
|
Sign up to set email alerts
|

Application of Three-Dimensional Culture Conditions to Human Embryonic Stem Cell-Derived Definitive Endoderm Cells Enhances Hepatocyte Differentiation and Functionality

Abstract: Human embryonic stem cells (hESCs) and induced pluripotent stem cells (iPSCs) provide an unlimited source for the generation of human hepatocytes, owing to their indefinite self-renewal and pluripotent properties. Both hESC-/ iPSC-derived hepatocytes hold great promise in treating liver diseases as potential candidates for cell replacement therapies or as an in vitro platform to conduct new drug trials. It has been previously demonstrated that the initiation of hESC differentiation in monolayer cultures increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 27 publications
5
53
0
Order By: Relevance
“…Different strategies have been used to improve the level of differentiation of the HLCs in vitro, such as the use of special matrix, 3D culture, spheroids formation, or coculture with stromal cells (46)(47)(48)(49)(50)(51)(52). However, none of them so far allowed maturation of the HLCs at a level similar to that of PHHs.…”
Section: Discussionmentioning
confidence: 99%
“…Different strategies have been used to improve the level of differentiation of the HLCs in vitro, such as the use of special matrix, 3D culture, spheroids formation, or coculture with stromal cells (46)(47)(48)(49)(50)(51)(52). However, none of them so far allowed maturation of the HLCs at a level similar to that of PHHs.…”
Section: Discussionmentioning
confidence: 99%
“…However, Matrigel, which is of biological origin with batch-to-batch variations, is still commonly used for the coating of culture vessels. 117,134,137 To enable better defined culture conditions, Matrigel was replaced in a number of studies by defined matrix components such as E-cadherin, 111,141 vitronectin, 142 or laminin. 107 A further possibility to increase reproducibility is to substitute recombinant growth factors with small molecules during the hepatic differentiation of pluripotent stem cells.…”
mentioning
confidence: 99%
“…Across a panel of 15 compounds that were known non-carcinogens, genotoxic carcinogens, and non-genotoxic carcinogens, gene expression analysis identified a subset of ϳ600 genes that separated the classes with 95% confidence and yielded biologically meaningful classification. The gene set identified also highly correlated with expression profiles from primary human hepatocytes (63). Another publication showed that hPSC-derived hepatocytes were sensitive to D-galactosamine hepatotoxicity, which could be attenuated by prostaglandin E 1 (67).…”
Section: Hepatocytesmentioning
confidence: 79%
“…Additionally, ␣-fetoprotein levels dropped and CYP3A4 levels increased after 8 weeks of culture of hPSC-derived hepatocytes (62). The re-creation of a three-dimensional matrix environment and the use of coculture with stromal cells also appeared to increase the differentiation and function of hPSC-derived hepatocytes (63,64). Although others have used genetic engineering to express hepatic transcription factors such as HNF4␣ to drive maturation (65), the use of small molecule "modifiers" is common in differentiation protocols and could similarly be used to enhance the maturation status of hPSC-derived hepatocytes (66).…”
Section: Hepatocytesmentioning
confidence: 98%